Laboratory Manual for Practical Biochemistry: tutorial : [practical book for students studying in the basic vocational and educational programs - specialty programs: "General Medicine"]Лабораторный практикум по биохимии: учебное пособие [для студентов, обучающихся по основным профессионально-образовательным программам - программам специалитета: "Лечебное дело"] - Носарева, О. Л. биохимия 19771006 Ольга Леонидовна (SibMed, 2024)
Biochemistry is a constantly changing and evolving academic discipline that requires continuous study to keep one's knowledge current. The practical book is written in accordance with the Federal State Educational Standard of Higher Professional Education for students studying in the basic vocational and educational programs - specialty programs: "General Medicine". There are laboratory works in each unit, which should be carried out by students during their practical lessons. The methods presented in the tutorial are used in clinical diagnostic laboratories. They assist the physician to diagnose the disease and to monitor the efficacy of treatment. Each unit is divided into several parts: questions for self-study, test tasks and case studies for testing the knowledge gained. The tutorial contributes to the formation of professional competencies, as well as the identification of the patient's basic pathologies, clinical signs, disease syndromes, nosologies.